Repeatability of reclaimed asphalt pavement - Mohd. Satar, Mohd. Khairul Idham (2016)
Usage of fresh bitumen and aggregates in pavement construction and rehabilitation can be minimised by utilising reclaimed asphalt pavement (RAP). RAP is a waste material generated from old or damaged pavement surface. Although it has been practiced since 1970s and several suggestions on the usage of RAP in the new mixture have been introduced, there is a limited number of research has been found, discussing on the issue of second recycling of RAP (R2AP). Pavement made with RAP will reach the end of service life and there is a need to recycle again. This study focused on investigating the performance of mixtures incorporating RAP and R2AP. It was carried out in three phases. In the first phase, three ageing procedures consisted of eight laboratory ageing methods were conducted to select suitable method that produced most severe ageing effect. Ageing methods used were combination of rolling thin film oven (RTFO), pressure aging vessel (PAV), short term oven ageing (STOA) and long term oven ageing (LTOA). In the second phase, mixture tests were conducted to evaluate the performance of asphaltic concrete with 14 mm nominal maximum aggregate size (AC 14) mixture incorporating RAP and R2AP. Final phase involved the physical, rheological and chemical property tests of aged bitumen. Penetration, softening point, viscosity, dynamic shear, elemental analysis and Fourier transform infrared (FTIR) tests were performed on the bitumen which were extracted from the selected mixtures. Three mixtures consisted of 20, 40 and 60% RAP were evaluated in the first cycle and four mixtures consisted of 20, 40, 60 and 80% R2AP were evaluated in the second cycle. Results show that seven days of LTOA is the most suitable ageing method for AC 14. Mixture consisted of 40% RAP shows a better performance when it was mixed with 80-100 PEN (B1) bitumen whereas mixture with 60% RAP performed better with 60-70 PEN (B2) bitumen compared to other mixtures. After seven days of LTOA, mixture consisted of 40% R2AP mixed with B1 and 40% R2AP mixed with B2 show better performance compared to other recycled mixtures. Physical, rheological and chemical analyses of the extracted bitumen also indicated that there were acceptable differences between first and second cycle. Hence, it is proven that R2AP is suitable to be used as an alternative material to minimise the usage of fresh bitumen and aggregates. Based on regression model of aged bitumen properties, it can be concluded that RAP was suitable to be recycled up to second time.